X‐Ray Absorption Spectroscopy Probing of Gold Electro‐Oxidation Reveals Intermediate Surficial Au(I) - David Degerman; Sara Boscolo Bibi; Bernadette Davies; Vladimir Grigorev; Aleksandr Kalinko; Tony Hansson; Sergey Koroidov (ChemElectroChem)
While Au electro‐oxidation in acidic aqueous media on a phenomenological level proceeds directly from Au(0) to Au(III), it has previously been suggested that Au(I) states are intermediate species of the oxidation mechanism. Here, additional evidence for the transient Au(I) is provided by the probing the electro‐oxidation of Au electrode operando in a pH = 3 perchloric acid (HClO4) electrolyte by high‐energy‐resolution fluorescence‐detected X‐ray absorption near‐edge structure (HERFD–XANES) at potentials up to 1.8 V versus the reversible hydrogen electrode (RHE). The perchlorate ions (ClO4−) in the electrolyte are used as sacrificial oxidizing agents. The reduced perchlorate compounds in turn produce chloride ions, which react with Au ions to form Au–Cl compounds. The operando HERFD–XANES detects and identifies the chlorinated compounds as surficial Au(I), present during the early stages of Au oxidation. It is further inferred that Au(I) is accessed by the electrolyte. These observations are consistent with the previously hypothesized route for Au electro‐oxidation involving charge transfer after a dipole‐induced place‐exchange step.